2020
DOI: 10.2478/picbe-2020-0081
|View full text |Cite
|
Sign up to set email alerts
|

Lean and Agile model implementation for managing the supply chain

Abstract: Even though both researchers and practitioners propose several approaches to supply chain management research and the scientific literature shows that several methods have been implemented for supply chain management, the studies carried out have not revealed a formalized process or a clear method for supply chain integration. Indeed, there is a specific way to achieve this integration in the supply chain and there are differences in how one company does it compared to another. More recently, an alternative ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Hassani, Ceauşu and Iordache [55] on the other hand in their study on lean and agile model implementation for managing the supply chain found that volatile and unpredictable environments demand supply chains that minimize waste and ensure flexibility, as was the case in the findings of this study.…”
Section: Waste Managementsupporting
confidence: 61%
“…Hassani, Ceauşu and Iordache [55] on the other hand in their study on lean and agile model implementation for managing the supply chain found that volatile and unpredictable environments demand supply chains that minimize waste and ensure flexibility, as was the case in the findings of this study.…”
Section: Waste Managementsupporting
confidence: 61%
“…The ultimate objective of lean production is to achieve better results with fewer labor hours and lower costs. This approach is most effective in environments with relatively stable and predictable demand and limited product variety [17][18][19]104].…”
Section: Lean Supply Chainmentioning
confidence: 99%
“…Supply chains' robustness and efficiency are essential to the world economy's revival. The development of policies and programs that support the recovery of economies and guarantee the free flow of products and services (Hassani, Ceauşu & Iordache, 2020).…”
Section: Significance Of Studymentioning
confidence: 99%
“…According to Hassani et al (2020), studies on lean and agile methodologies, their outcomes and potential future avenues of inquiry must be conducted and evaluated to enhance supply chain management. The ability to act, react, and conform to changes in economic conditions can be improved by combining the Agility and Lean paradigms, which are distinguishable and can be formed in their ways, to a well-planned supply chain collaboration that incorporates a considerable extent of uncertainty in terms of importance and threshold of implementation across various supply chains.…”
Section: Global Supply Chain Matrixmentioning
confidence: 99%